Pengaruh Media Sosial dan Komunikasi Publik Gubernur terhadap Opini Publik (Studi Analisis Regresi Pada Kepemimpinan Gubernur Kepulauan Bangka Belitung Periode 2017-2022) - Anindita, Listya (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This study aims to analyze the influence of social media and public communication of the governor on public opinion, using regression analysis on the leadership of the Governor of Bangka Belitung Islands for the period 2017-2022. The research method used is quantitative with a positivist paradigm. The population of this study is the residents of Bangka Belitung aged 17 years and above, who have the right to vote, amounting to 913,239 people. The multistage cluster sampling technique was used to obtain a sample of 600 respondents. The data analysis technique used is multiple regression analysis. The results of the coefficient of determination test which aims to measure the percentage influence of social media and the governor's public communication on public opinion indicates 19.6%, the remaining 80.4% of the variables in public opinion still cannot be explained by the variables in this research. The correlation coefficient is 0.443. This value shows that there is a positive relationship between social media variables and public communication with a moderate influence on public opinion variables. The results of testing the statistical significance of the variable influence of social media and public communication on public opinion have a positive and significant effect.